The Great Recession and SNAP Caseloads: A Tale of Two States. Issue 3 (2nd July 2016) - Edwards, Mark; Heflin, Colleen; Mueser, Peter; Porter, Suzanne; Weber, Bruce
ABSTRACT: Using detailed administrative data for the 2003 to 2010 period, the authors contrast Florida's and Oregon's dramatically different participation dynamics, assessing the expansion and extension of benefits before, during, and after the Great Recession. State differences in how Supplemental Nutrition Assistance Program (SNAP) has been administered help explain differences in SNAP use. Although the recession led to increased need and SNAP participation in both states, state differences in prerecession program policies and efforts to enroll and retain eligible participants provide a plausible explanation for lower exit rates and longer spell durations in Oregon. Implications of these findings for low income households, policymakers and future research are discussed.